Dampak Just in Time pada Inventory Management Studi Kasus pada Industri Manufaktur Automotive - Goo, Maria Alni Lau; Aldi, Mukhamad Fauzan; Wibowo, Febrian Dimas J.; Hatuina, Suci Harira Sari; Riyadi, Slamet; Pandin, Maria Yovita R. (MES Bogor, 2024)
The purpose of this study is to determine the Impact of Just In Time on Inventory Management Case Study in the Automotive Manufacturing Industry by determining the key factors that are fundamental to just in time practices. This research was conducted in two automotive manufacturers serving the sector hereinafter referred to as Company A and Company B, as these companies cannot be named, for this reason, the identity of these companies cannot be revealed. The approach used here is a mixed approach of quantitative research and qualitative methodology. From the study it can be concluded that organizations can have lower performance or efficiency in managing or controlling inventory, when not implementing JIT or Just-Time practices. In addition, we can also see how JIT affects inventory management practices in organizations in a positive way. This further leads to a positive perception of business performance from both employees and management of the organization. The results for Company A show better performance with cost effective performance through the implementation of the JIT system, with employees being more aware of the inventory management practices in place and the changes and benefits being transmitted to the system